Measuring changes in activity participation of older Australians: Validation of the Activity Card Sort – Australia - Doney, Robyn; Packer, Tanya (Blackwell Publishing Asia, 2008)
Objectives: This study explored the psychometric properties of the Australian version of the Activity Card Sort (ACS-Aus), a recently developed measure of activity participation for use with older adults. Concurrent, convergent construct, and discriminative construct validity were examined. Methods: The study included 93 Australian adults aged 60–95 years. Participants completed the ACS-Aus, as well as an existing Australian measure of activity participation (The Adelaide Activities Profile) and an Australian measure of subjective well-being (the Personal Well-being Index). Results: The ACS-Aus demonstrated moderate concurrent validity (r = 0.434), moderate convergent construct validity (r = 0.354), and strong discriminative validity (P = 0.000). Conclusions: The World Health Organization has recently promoted participation as an important component of the healthy ageing process. This study has validated the use of the ACS-Aus in measuring participation of community-dwelling older adults in Australia.